Is synovitis detected on non-contrast-enhanced magnetic resonance imaging associated with serum biomarkers and clinical signs of effusion? Data from the Osteoarthritis Initiative. (4th May 2018) - Deveza, LA; Kraus, VB; Collins, JE; Guermazi, A; Roemer, FW; Nevitt, MC; Hunter, DJ
Abstract : Objectives : To determine the relationship between synovitis detected on non-contrast-enhanced (non-CE) magnetic resonance imaging (MRI), biochemical markers of inflammation, and clinical assessment of effusion in people with knee osteoarthritis (OA). Method : We examined data from the OA Biomarkers Consortium within the Osteoarthritis Initiative (n = 600). Non-CE MRIs were semi-quantitatively scored (grades 0–3) for severity of Hoffa synovitis and effusion synovitis. Serum (s) matrix metalloproteinase-3 (sMMP-3), hyaluronic acid (sHA), and nitrated epitope of the α-helical region of type II collagen (sColl2-1NO2) were quantified. The bulge and patellar tap clinical tests were performed at baseline and performance characteristics were assessed for the detection of effusion synovitis on MRI. Multinomial logistic regression adjusted for covariates was used to assess the association between biochemical and imaging markers at baseline and over 12 and 24 months. Results : At baseline, sHA and sMMP-3 were associated with moderate to large (score ≥ 2, n = 117) effusion synovitis, with odds ratio = 1.35 and 1.30 per 1 standard deviation in biochemical markers (95% confidence intervals 1.07, 1.71 and 1.00, 1.69), c-statistics 0.640 and 0.626, respectively. The c-statistics for the presence of Hoffa synovitis (score ≥ 2) were 0.693, 0.694, and 0.694 for sHA, sMMP-3, and sColl2-1NO2, respectively. There was no significant association between biochemical markers (baseline and 12 and 24 month time-integrated concentrations) and changes in MRI markers. The bulge and patellar tap signs were 22.0% and 4.3% sensitive and 88.8% and 94.8% specific, respectively, for detecting effusion synovitis (score ≥ 1) on MRI. Conclusions : sHA and sMMP-3 were modestly associated with effusion synovitis at baseline. Clinical signs of effusion are insensitive but highly specific for the presence of any effusion synovitis on non-CE MRI.